A Source of WRF Simulation Error for the Early‐Summer Warm‐Sector Heavy Rainfall Over South China Coast: Land‐Sea Thermal Contrast in the Boundary Layer. Issue 4 (22nd February 2022) - Gao, Xiaoyu; Luo, Yali; Lin, Yanluan; Bao, Xinghua
Abstract: Quantitative prediction of the early‐summer warm‐sector heavy rainfall over South China coast (SCC) is still a challenge. This study conducts convection‐permitting Weather Research and Forecast model simulations for a representative nocturnal‐to‐morning heavy rainfall event related to low‐level jets during 29–30 May 2020, and explores sources of simulated rainfall bias using multi‐source observations, reanalysis data and sensitivity experiments. Results show that the model initiated about 12 hr before the coastal convection initiation only produces sporadic convection and misses the heavy rainfall at SCC, although it captures the major synoptic features as in previous studies. The underestimated convection development is closely related to insufficient convergence of boundary layer (BL) wind due to overestimated speed of the onshore BL wind. Increasing the land surface friction effects in the simulations through either multiplying the surface roughness length by 10 or including sub‐grid topography drag effects could help little suppress the simulated biases. Using hourly data assimilation to improve the simulation of marine/land BL temperature from the afternoon to nighttime produces a desired change in the nocturnal BL wind across the coastline and significantly improves rainfall simulation with the maximum and average rainfall over SCC increased by about 4 and 6.5 times, respectively. These findings indicate that, to improve the prediction of the nocturnal heavy rainfall in the warm‐sector over SCC during early summer, it is necessary to more accurately predict the BL thermal structure during the daytime, in addition to the previously emphasized nocturnally enhanced marine BL flow. Key Points: Multi‐source observations show an overestimation of boundary layer (BL) wind in Weather Research and Forecast simulation of warm‐sector heavy rainfall on South China coast (SCC) Better modeling the land/sea BL temperature enhances the BL wind convergence and reduces the underestimation of SCC rainfall at night Increasing the land surface friction could help little suppress the simulated biases in the onshore BL wind and the SCC heavy rainfall